Effects of commercial and farm-made inoculants on the chemical composition and fermentation of kikuyu grass silages - Villalobos Villalobos, Luis Alonso (2022)
Ensiling allows for more efficient pasture utilization in kikuyu (Cenchrus clandestinus Hochst. ex Chiov.)-based forage systems. However, the chemical composition of kikuyu challenges this process. Additives can improve the quality of kikuyu silage. This study aimed to evaluate how the organoleptic, fermentative, and nutritive traits of kikuyu (90-d regrowth) were affected by three inoculants [farm-made inoculants (FMI), Efficient Microorganisms (EMI), and a commercial inoculant] compared with a control. We hypothesized that FMI and EMI would perform similarly to the commercial inoculant on kikuyu silage. The control treatment had lower scores for odor, but texture, moisture and color were adequate and similar among treatments. Kikuyu silage had similar concentrations of ammonia nitrogen (2.72–3.23%) among treatments, with the pH (5.04–5.20) and buffering capacity [95–111 meq NaOH 100 g–1 dry matter (DM)] indicating resistance to acidification. The DM of kikuyu silage (20.7–21.0%) was similar to the forage prior to ensiling. The crude protein (8.13–8.69%) and ash (15.5–16.8%) concentrations indicated the forage's advanced maturity and were not affected by the inoculants. Mean neutral detergent fiber (NDF) was similar for FMI and EMI (54.8 and 54.8%) compared with the control and commercial inoculant (58.5 and 62.8%), and kikuyu silage had lower concentrations than fresh forage. In vitro DM digestibility was similar among treatments (55.7–59.0%). There was no clear advantage of using inoculants to ensile kikuyu grass, but the variation in NDF and hemicellulose concentrations in the control treatment suggests that kikuyu silages may benefit from inoculants.